Plasma and fecal hormone profiles in an Endangered, oviparous colubrid, the Louisiana pinesnake. - M M Richter; B M Roberts; M R Sandfoss; S B Reichling (PLoS ONE, 2025)
Reptiles are sorely under-represented in endocrinology research. The majority of studies are conducted on lizards and turtles, rarely are oviparous snakes investigated. We utilized our breeding population of captive Louisiana pinesnakes (Pituophis ruthveni, LPS) to describe annual hormone cycles in an egg-laying colubrid. We collected fecal and blood samples from adult male and female snakes (20M.23F) throughout the year. After validating extraction methods and assays, we measured four hormones (corticosterone, estradiol, progesterone, and testosterone) in samples collected (200 + fecal and 600 + blood samples) over a two-year period. While blood samples were collected on a schedule, fecal samples were collected opportunistically. We found differences in patterns exhibited by males and females and between sample types. In females, neither fecal nor plasma samples showed significant differences between any of the collection periods, excepting increased levels found in female plasma progesterone PreLay compared to PostLay (n = 4 animals, p = 0.0323) demonstrating the importance of circulating progesterone in oviparous snake reproduction. In males, time played a significant role in fecal corticosterone levels (p = 0.0164). Male plasma showed a number of significant changes throughout the year: a significant increase from Post-Brumation to Breeding levels of corticosterone (p = 0.0058), Breeding estradiol and testosterone levels significantly higher (E2: p < 0.036, T: p < 0.005) than all other time bins except Post-Brumation (E2: p = 0.062, T: p = 0.1). Comparing differences and similarities between two different sample types, there is a clear advantage to collecting blood on a set schedule; we were able to analyze samples based on significant life history events and maintain larger sample sizes which may have contributed to the lack of differences measured in fecal hormone levels. This study helps to better understand the seasonal hormonal patterns in egg-laying snakes, and to aid in the recovery of this endangered species.